Lumen and mucosa-associated Lactobacillus rhamnosus from the intestinal tract of organ donors. (10th November 2020) - Marsh, Alan J.; Yaya, Al-Mounawara A.; Ng, Sandy; Chandrashekhar, Kshipra; Roach, Jeff; Magness, Scott T.; Azcarate-Peril, M. Andrea
ABSTRACT: Knowledge of the intra-individual spatial and regional distribution of intestinal microbial populations is essential to understand gut host–microbial interactions. In this study, we performed a compositional analysis of luminal and mucosal samples from the small and large intestine of four organ donors by 16S rRNA amplicon sequencing and high-throughput quantitative polymerase chain reaction. Since the human microbiota is subject to selection pressure at lower taxonomic levels, we isolated over 400 bacterial strains and investigated strain-level variation of 11 Lactobacillus rhamnosus from different intestinal regions. Results substantiate reported inter-individual variability as well as intra-individual differences along the gastrointestinal tract. Although the luminal and mucosal-associated communities were similar within individuals, relative abundance reflected the donors' demographic and potential pathologies. The total bacterial load of all donors increased from small intestine to colon, while Bifidobacterium was in greater abundance in the small intestine. Comparative genomic analysis of L. rhamnosus showed the strains segregated into two distinct clusters and identified no features specific to location. Analysis revealed genetic differences for exopolysaccharide production, carbohydrate utilization, pilus formation and vitamin K biosynthesis between clusters. This study contributes to the understanding of niche-specific microbial communities, encouraging subsequent studies to better understand microbial signatures at lower taxonomic levels.